2021
DOI: 10.1002/cncr.33457
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality‐of‐life assessment of patients with solid tumors on immuno‐oncology therapies

Abstract: Immuno‐oncology therapies have been approved for various solid tumors; however, the high cost of these treatments and their potential toxicities require a thorough assessment of their risks and benefits. Collection of data directly from patients through patient‐reported outcome instruments can improve the precision and reliability of adverse event detection, assess tolerability of adverse events, and provide an evaluation of health‐related quality of life (HRQOL) changes from immuno‐oncology therapies. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Despite the importance of HRQoL of patients following immunotherapy, it has only received some limited, recent research attention [ 21 , 22 ]. One noticeable gap is that less HRQoL-focused research has been performed regarding cancer immunotherapy purely due to the treatment’s relative novelty.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of HRQoL of patients following immunotherapy, it has only received some limited, recent research attention [ 21 , 22 ]. One noticeable gap is that less HRQoL-focused research has been performed regarding cancer immunotherapy purely due to the treatment’s relative novelty.…”
Section: Introductionmentioning
confidence: 99%
“…In In our study, we tried to evaluate the quality of life of cancer patients who underwent the method of ICI, as other researchers have done in the past [18][19][20][21]. Similar studies, also, have found a statistically significant association between socioeconomic and demographic characteristics and quality of life in cancer patients, such as marital status, age, and gender [22][23][24][25].…”
Section: Demographic Characteristicsmentioning
confidence: 87%
“…As one ODAC member noted during the 2019 review of selinexor, such instruments are static and may be limited in their ability to capture important study-specific concepts (Table 3). Recent publications have observed this limitation, pointing out several legacy instruments that do not capture symptomatology unique to immune checkpoint inhibitors [35][36][37] and targeted therapies. 38 Furthermore, legacy measures may not have been validated in specific groups of patients.…”
Section: Discussionmentioning
confidence: 99%